A study on service quality of information technology with reference to private and public sector banks in thoothukudi district - C, PACKIALAKSHMI (Journal of Management and Science, 2013)
The financial reforms that were initiated in the early 1990s and the globalization and liberalization measures brought in a completely new operating environment to the banks. The bankers are now offering innovative and attractive technology based services and products such as Anywhere Banking, Anytime Banking, Telebanking, Internet Banking, Web Banking ect., to their customers to cope with the competition. Internet banking is a new delivery channel for banks in Thoothukudi. Technology plays a vital role in improving the quality of services provided by the business units. Advent and adoption of internet by the industries has removed the constraint of time, distance and communication making globe truly a small village. Financial sector being no exception, numerous factors such as competitive cost, customer service, increase in education and income level of customers, etc. Influence banks to evaluate their technology and assess their electronic commerce and internet banking strategies. Internet banking allows banking from anywhere, anytime and is used for transactions, payments etc. over the internet through a bank, a credit union or society‘s secure website. The Service industries are mostly customer driven and their survival in competitive environment largely depends on quality of the service provided by them. In this context, quality of service furnished by banking sector is very important and profitability of their business is closely connected to the quality ofservice.